Characterization and detached-leaf pathogenicity of representative pestalotioid fungal isolates from symptomatic rubber leaves in selected areas of Sumatra, Indonesia - FARRIZA DIYASTI; WEN DEE ONG; TSABITAH SITI RAHMA; ACHMAD EKA SATRIA; TRI RAPANI FEBBIYANTI; STEPHANY ANGELIA TUMEWU; FITRINE EKAWASTI; MINAMI MATSUI; NEO ENDRA LELANA; WELLYZAR SJAMSURIDZAL; RETNO LESTARI (Society for Indonesian Biodiversity, 2026)
Abstract. Diyasti F, Ong WD, Satria AE, Febbiyanti TR, Tumewu SA, Ekawasti F, Matsui M, Lelana NE, Sjamsuridzal W, Lestari R. 2026. Characterization and detached-leaf pathogenicity of representative pestalotioid fungal isolates from symptomatic rubber leaves in selected areas of Sumatra, Indonesia. Biodiversitas 27 (8): d270809. https://doi.org/10.13057/biodiv/d270809. Pestalotioid fungi have emerged as important pathogens associated with rubber leaf fall disease in Indonesia. This study characterized the morphological traits, molecular identity, and pathogenicity of five representative pestalotioid fungal isolates, each selected from a different sampling location across four major rubber-producing provinces in Sumatra (Riau, Jambi, South Sumatra, and Bangka Belitung). Five representative isolates (P_R.SS1, P_R.JM, P_R.BB, P_R.SS2, and P_R.RA) were selected for detailed morphological, molecular, and pathogenicity analyses. Morphological observations revealed variation in colony color, growth rate, and conidial dimensions. Molecular identification based on Internal Transcribed Spacer (ITS) rDNA sequences assigned the isolates to the genera Neopestalotiopsis and Pseudopestalotiopsis. Pathogenicity testing using a detached-leaf assay on Hevea brasiliensis clone PB260 revealed significant differences in lesion development among the five representative isolates at 7 days post-inoculation. Isolate P_R.RA from Riau produced the largest necrotic lesion area (0.802±0.332 cm²) despite exhibiting the slowest in vitro colony growth rate (35.807±1.56 cm²), whereas isolates P_R.SS1, P_R.JM, and P_R.BB produced lesion areas below 0.06 cm². These results indicate differences in pathogenicity among the representative isolates examined in this study. These findings provide preliminary baseline information for future multilocus identification and broader investigations of pestalotioid fungi associated with rubber leaf fall disease.